Determinants Of Satyagraha Msme Performance In Bali Province - Yogapramana, I Wayan Bayu; Widiana, I Nyoman Wahyu; Yuliantari, Pande Putu Ida (Universitas Mercu Buana, 2024)
This research was conducted with the aim of determining the influence of financial literacy, capital aspects, quality of human resources, and marketing on the performance of Satyagraha MSMEs in Bali Province, both partially and simultaneously. The sample size was calculated using the Slovin method, resulting in 93 units of Satyagraha MSMEs from a population of 1,250 units of Satyagraha MSMEs in Bali Province. The selection of respondents was carried out by purposive sampling. The research method used is quantitative with data collection through the distribution of questionnaires. This research was conducted on Satyagraha MSMEs located in Bali Province. The data used is sourced from primary and secondary data. The data processing method used is multiple linear regression analysis. The results shown in this study are financial literacy, capital aspects, quality of human resources, and marketing have a positive and significant partial and simultaneous effect on the performance of Satyagraha MSMEs in Bali Province. The researcher's advice to Satyagraha MSME actors is to maintain and improve financial literacy, capital aspects, quality of human resources, and marketing owned. And the next researcher is advised to consider other variables that allegedly affect the performance of Satyagraha MSMEs.